Perlawanan Puisi Sittun ‘Aman karya Tamim al-Borghouti terhadap Rezim Zionis di Jalur Gaza - Muhammad Jafar Shiddiq; Moch. Rofiuddin (Diwan: Jurnal Bahasa dan Sastra Arab, 2024)
Arabic poetry has evolved in its function over time, encompassing more than just romantic words, praise, pride, or lamentation. It now includes themes of resistance, revolutionary milestones, and struggles. This study focuses specifically on Tamim al-Borghouti's poem, "Sittun 'Aman," and its resistance against the Zionist regime in the Gaza strip. Riffaterre's semiotic perspective is used to analyze and interpret the verses of the poem through heuristic and hermeneutic readings. The findings of this study consist of a heuristic reading that identifies stanzas containing words of resistance, as well as a hermeneutic reading that reveals the poem's advocacy for freedom, justice, and humanist morality. It emphasizes that this freedom is not limited to a particular group but is inclusive and rejects fanaticism. Additionally, the poem criticizes the United Nations world government for its failure to effectively address human rights violations. This criticism stems from the disconnect between the goals set by the United Nations and the reality of events, particularly those occurring in the Gaza strip.